2020
DOI: 10.3346/jkms.2020.35.e346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Early Extubation Strategy in Patients Undergoing Extracorporeal Membrane Oxygenation as a Bridge to Heart Transplantation

Abstract: Background Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) might be considered a bridge therapy in patients who are expected to have short waiting times for heart transplantation. We investigated the clinical outcomes of patients who underwent VA-ECMO as a bridge to heart transplantation and whether the deployment of an early extubation ECMO strategy is beneficial. Methods Between November 2006 and December 2018, we studied 102 patients who received VA-ECMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…In our study, the median time of mechanical ventilation to first extubation of all patients was 45 (2-918) hours, and 28% were extubated in less than 24 hours after ECMO implantation, which supports the adherence to the early extubation protocol, whenever possible. However, in line with the study by Youn et al, 26 the occurrences the most catastrophic adverse event among our patients with 100% hospital mortality.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the median time of mechanical ventilation to first extubation of all patients was 45 (2-918) hours, and 28% were extubated in less than 24 hours after ECMO implantation, which supports the adherence to the early extubation protocol, whenever possible. However, in line with the study by Youn et al, 26 the occurrences the most catastrophic adverse event among our patients with 100% hospital mortality.…”
Section: Resultssupporting
confidence: 92%
“…The summary of the "Awake ECMO" strategy by Langer et al 25 describes several benefits of re duced mechanical ventilation time, with the key being the prevention of ventilator induced dia phragm dysfunction and ventilator associated pneumonia. Recently, Youn et al 26 reported in hospital mortality rates for deferred extubation (>48 hours) and early extubation (≤48 hours) in ECMO patients, as 24.4% and 8.3%, respective ly. In our study, the median time of mechanical ventilation to first extubation of all patients was 45 (2-918) hours, and 28% were extubated in less than 24 hours after ECMO implantation, which supports the adherence to the early extubation protocol, whenever possible.…”
Section: Resultsmentioning
confidence: 99%
“…The ECLS modality support, when reported, was venoarterial (V-V) in 56.8% (n = 619/1089) 14,[19][20][21][25][26][27]29,31,32,38,[40][41][42][43]45,47 of patients, veno-venous (V-A) in 39.6% (n = 431/1089) 14,19,[22][23][24]26,30,[32][33][34][35][38][39][40][42][43][44][45][46] of cases and only 3.9% (n = 39/1089) 26,30,32,38,40,44,45 of patients underwent other ECLS modalities. Cannulation strategy was reported in 931 cases (80.5% of the total population reviewed).…”
Section: Common Practice Definition Evaluation Scoresmentioning
confidence: 99%
“…Main indications for ECLS support were BTR (n = 666, 36.6%) 19,[22][23][24][25][27][28][29][30][31][33][34][35]37,39,41,[43][44][45][46] and BTT (n = 472, 34.8%). 14,21,23,24,26,28,32,[35][36][37][38]40,42,[45][46][47] 14,34,38,39,41,46 and ranged 20-30.1.…”
Section: Patients and Ecls Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation